Early Christian Identity Formation: From Ethnicity and Theology to Socio-Narrative Criticism - Baker, Coleman A. (Currents in biblical research, 2011)
In this article, the author traces four trajectories in which early Christian identity formation has been studied in the nineteenth and twentieth centuries: ethnicity, theology, social-scientific, and literary. The author concludes by suggesting a way forward that includes interdisciplinary work that combines the insights of these four trends.